Evidence regarding the ecological benefits of payment for ecological services programs from China’s grassland ecological compensation policy - Wei, Cong; Zhou, Yingfeng; Kong, Jiayang (Frontiers in Environmental Science, 2022)
We provided evidence that payment for ecological services programs had a significant and robust positive impact on grassland quality by focusing on China’s grassland ecological compensation policy, which is the planetary largest one. Our baseline results are obtained from a difference-in-differences estimator, comparing counties with and without introducing grassland ecological compensation policy, showing that grassland ecological compensation policy increases grassland quality by about 4 percentage points on average. We found a similar impact of grassland ecological compensation policy on grassland quality when we controlled for the estimated propensity of a county to launch the grassland ecological compensation policy based on a series of county characteristics, such as weather and economic conditions. We obtained comparable estimates when we used the propensity score as weights to balance county characteristics between counties with and without launching the grassland ecological compensation policy. Our results also show that grassland ecological compensation policy has a larger impact on grassland quality in warmer, richer, and less population counties than those with opposite characteristics. We found strong suggest for the persistence of the impact that grassland ecological compensation policy had on grassland quality, implying that the Chinese officials should persist launching the grassland ecological compensation policy, and expand the range of pilot policy. In addition, we carried out a series of robustness tests, including the leave-one-county-out test, the bootstrapping test, and the permutation test, to illustrate the robustness of our results.